2001
DOI: 10.1081/css-100104102
|View full text |Cite
|
Sign up to set email alerts
|

Furrow Irr Igation and N Management Strategies to Protect Water Quality

Abstract: N management under furrow irrigation is difficult because nitratenitrogen (NO3-N) is frequently leached to groundwater. Banding and sidedressing N fertilizer on a non-irrigated side of a row of corn (Zea mays L.) might increase N uptake and minimize nitrate leaching potential by reducing the NO 3-N in soil profiles at harvest, thereby protecting water quality. For two years in the field, we evaluated two N placements (broadcast vs. banded), two row spacings (0.76-m vs. a modified 0.56-m), and two ways of posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…This finding was consistent across both row spacings because row spacing did not significantly alter this interaction (Table 2). Lehrsch et al (2001) found that NO 3 –N in soil profiles to a depth of 0.9 m under corn rows was least in 1989 where N was banded, rather than broadcast, and where the nonfertilized furrow was irrigated, also suggesting a greater N use efficiency under these conditions. Where N was broadcast into the N‐depleted profile in 1989 and the same furrow was irrigated, the root development (and to a limited degree, the N uptake via mass flow) may have been inhibited in relatively dry soil under the nonirrigated furrow.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This finding was consistent across both row spacings because row spacing did not significantly alter this interaction (Table 2). Lehrsch et al (2001) found that NO 3 –N in soil profiles to a depth of 0.9 m under corn rows was least in 1989 where N was banded, rather than broadcast, and where the nonfertilized furrow was irrigated, also suggesting a greater N use efficiency under these conditions. Where N was broadcast into the N‐depleted profile in 1989 and the same furrow was irrigated, the root development (and to a limited degree, the N uptake via mass flow) may have been inhibited in relatively dry soil under the nonirrigated furrow.…”
Section: Discussionmentioning
confidence: 93%
“…From these N‐depleted profiles in 1989, soil N may not have been scavenged efficiently in 0.56‐m plots because the roots were likely concentrated under each pair of 0.56‐m rows, and thus were relatively sparse between each pair of 0.56‐m rows (Fig. 2) Alternatively, the closer proximity of the irrigation furrows to the N fertilizer in 0.56‐m rows may have led to more leaching of both the fertilizer and limited residual soil N in the 1989 profiles (Lehrsch et al, 2001) The generally 35% larger irrigations in 1989 than in 1988 (Fig. 3) may have sufficiently increased NO 3 –N leaching under the 0.56‐m rows to reduce the yield in 1989 but not in 1988 (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the spatial separation of water and fertilizer can reduce N leaching (Kemper et al, 1975; Xing et al, 2002). Lehrsch et al (2001) and Skinner et al (1998, 1999) have demonstrated that N leaching can be reduced by applying N fertilizer to the unirrigated furrow under fixed partial root‐zone irrigation. Computer simulations by Benjamin et al (1997) predicted that less N movement into deeper soil layers would occur if alternate furrow irrigation was managed with N fertilizer placement in the unirrigated furrow.…”
mentioning
confidence: 99%